The Impact of ACE Inhibitors and Angiotensin Receptor Blockers on Aerobic Capacity and VO2 Max in Patients Undergoing Endurance Training - Kowalski, Mateusz; Rucki, Michał; Cieleban, Nikodem; Rucka, Aleksandra Maria; Modliborska, Magdalena (Quality in Sport, 2026)
Background. Angiotensin-converting enzyme inhibitors (ACEi) and angiotensin receptor blockers (ARBs) are foundational pharmacological therapies for hypertension and cardiovascular diseases. However, their potential interference with physiological adaptations to endurance training, particularly maximal aerobic capacity (VO2 max), remains a critical concern for clinicians and athletes. Aim. This review aims to synthesize the current evidence regarding the impact of ACEi and ARB therapy on VO2 max, hematological parameters, and cardiac remodeling in patients and healthy individuals undergoing structured endurance training. Material and methods. A narrative review was conducted using PubMed, Google Scholar, and the archives of the Journal of Education, Health and Sport and Quality in Sport. Search terms included "ACE inhibitors," "angiotensin receptor blockers," "VO2 max," and "endurance training." Inclusion criteria focused on peer-reviewed articles published between 2015 and 2025, emphasizing human clinical trials and systematic reviews. Results. Evidence suggests that while chronic RAAS inhibition does not significantly attenuate relative VO2 max gains in hypertensive populations or those with metabolic syndrome, it may compromise specific physiological determinants. Notably, ACEi treatment has been associated with a reduction in total hemoglobin mass expansion and a blunting of lean mass accrual. Furthermore, sex-specific responses indicate that women may experience a more pronounced inhibition of aerobic adaptations compared to men when using standard ARB dosages. Conclusions. ACEi and ARBs are generally compatible with aerobic exercise; however, their impact on hematological and morphological adaptations requires careful consideration, especially in high-performance or female cohorts. Exercise remains a vital synergistic co-therapy for managing hypertension alongside these medications.